Analgesic effect of 5-(3,4-dihydroxyphenyl)-3-hydroxy-1-(2-hydroxyphenyl)penta-2,4-dien-1-one in experimental animal models of nociception - Kamarudin, Nur Nadhirah; Hisamuddin, Nadia; Ong, Hui Ming; Ahmad Azmi, Ahmad Farhan; Leong, Sze Wei; Abas, Faridah; Sulaiman, Mohd Roslan; Shaik Mohamed Mossadeq, Wan Mastura (MDPI, 2018)
Curcuminoids derived from turmeric rhizome have been reported to exhibit antinociceptive, antioxidant and anti-inflammatory activities. We evaluated the peripheral and central antinociceptive activities of 5-(3,4-dihydroxyphenyl)-3-hydroxy-1-(2-hydroxyphenyl)penta-2,4-dien-1-one (DHHPD), a novel synthetic curcuminoid analogue at 0.1, 0.3, 1 and 3 mg/kg (intraperitoneal), through chemical and thermal models of nociception. The effects of DHHPD on the vanilloid and glutamatergic systems were evaluated through the capsaicin- and glutamate-induced paw licking tests. Results showed that DHHPD significantly (p < 0.05) attenuated the writhing response produced by the 0.8% acetic acid injection. In addition, 1 and 3 mg/kg of DHHPD significantly (p < 0.05) reduced the licking time spent by each mouse in both phases of the 2.5% formalin test and increased the response latency of mice on the hot-plate. However, the effect produced in the latter was not reversed by naloxone, a non-selective opioid receptor antagonist. Despite this, DHHPD decreased the licking latency of mice in the capsaicin- and glutamate-induced paw licking tests in a dose response manner. In conclusion, DHHPD showed excellent peripheral and central antinociceptive activities possibly by attenuation of the synthesis and/or release of pro-inflammatory mediators in addition to modulation of the vanilloid and glutamatergic systems without an apparent effect on the opioidergic system.